Primary care multidisciplinary teams in practice: a qualitative study - Leach, Brandi (BMC Fam Pract, 2017)
BACKGROUND: Current recommendations for strengthening the US healthcare system consider restructuring primary care into multidisciplinary teams as vital to improving quality and efficiency. Yet, approaches to the selection of team designs remain unclear. This project describes current primary care team designs, primary care professionals’ perceptions of ideal team designs, and perceived facilitating factors and barriers to implementing ideal team-based care. METHODS: Qualitative study of 44 health care professionals at 6 primary care practices in North Carolina using focus group discussions and surveys. Data was analyzed using framework content analysis. RESULTS: Practices used a variety of multidisciplinary team designs with the specific design being influenced by the social and policy context in which practices were embedded. Practices overwhelmingly located barriers to adopting ideal multidisciplinary teams as being outside of their individual practices and outside of their control. Participants viewed internal organizational contexts as the major facilitators of multidisciplinary primary care teams. The majority of practices described their ideal team design as including a social worker to meet the needs of socially complex patients. CONCLUSIONS: Primary care multidisciplinary team designs vary across practices, shaped in part by contextual factors perceived as barriers outside of the practices’ control. Facilitating factors within practices provide a culture of support to team members, but they are insufficient to overcome the perceived barriers. The common desire to add social workers to care teams reflects practices’ struggles to meet the complex demands of patients and external agencies. Government or organizational policies should avoid one-size-fits-all approaches to multidisciplinary care teams, and instead allow primary care practices to adapt to their specific contextual circumstances.